2021
DOI: 10.1016/j.jinf.2021.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Panbio™ rapid antigen test for SARS-CoV-2 has acceptable accuracy in symptomatic patients in primary health care

Abstract: Objectives: We aimed to evaluate the accuracy of the Panbio TM Ag-RDT at primary health care (PHC) centers and test sites in symptomatic patients and close contacts, using the Reverse-Transcription Polymerase Chain Reaction (RT-PCR) test as the gold standard. Methods: The study was conducted in four PHC centers and two test sites in Mallorca, Spain. Consecutive patients older than 18 years, attending the sites for RT-PCR testing were included. Two nasopharyngeal samples were collected, one for RT-PCR and the o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
33
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 14 publications
9
33
4
1
Order By: Relevance
“…Sensitivity and specificity of such antigen rapid diagnostic tests strongly depend on their good execution and reading which are harder to achieve at the frontline where the expertise of personnel can vary; especially in this time of pandemic when the turn-over is higher than usual. This was confirmed by other recently published studies targeting the same population, with sensitivity ranging from 70.0 to 80.4% (29)(30)(31).…”
Section: Discussionsupporting
confidence: 88%
“…Sensitivity and specificity of such antigen rapid diagnostic tests strongly depend on their good execution and reading which are harder to achieve at the frontline where the expertise of personnel can vary; especially in this time of pandemic when the turn-over is higher than usual. This was confirmed by other recently published studies targeting the same population, with sensitivity ranging from 70.0 to 80.4% (29)(30)(31).…”
Section: Discussionsupporting
confidence: 88%
“…There are over 10 clinical studies (8 preprints, 2 published) evaluating the performance of the Panbio™ Ag-RDT [3][4][5][6][7][8][9][10][11][12] using only manufacturer recommended NPS. Those studies, with over 6000 subjects, have reported sensitivity and specificity ranges of 71.4%-91.7% and 94.9%-100%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Those studies, with over 6000 subjects, have reported sensitivity and specificity ranges of 71.4%-91.7% and 94.9%-100%, respectively. Considering only Ct values <30 yielded test sensitivities from 87.7% to 97.8% [ 3 , 6 9 ]. Similarly, samples from <5 DPOS yielded a sensitivity between 77.2 and 94.8% [ 3 , 5 , 6 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have noted lower sensitivity in asymptomatic (48.1%-56.5%) individuals compared to symptomatic ones (71.4%-80.4%) [39][40][41][42] . Since Ag-RDT sensitivity is largely related to viral load, these differences might reflect dissimilarities in the kinetics of SARS-CoV-2 viral load in the upper respiratory tract.…”
Section: Discussionmentioning
confidence: 97%